A regional flow type classification for South African perennial rivers - NA Rivers-Moore; RE Schulze; NS Davis (Water SA, 2020)
Flow classification provides a statistically robust method of defining an expected range of variability for flow metrics describing frequency, magnitude, duration and timing of events.  Here, we characterised reference mean daily flows for 1950–1999 for all 5 838 quinary catchments of South Africa based on 150 metrics.  Using a two-tiered approach, where sub-catchments were classified into similar flow types using principal components and cluster analyses, we defined 6 to 12 flow types for each of 8 hydrological regions reflecting rainfall seasonality.  Redundancy between variables was 87% on average, so that site variability could be accounted for using 8–28 metrics.  In general, flow volume metrics accounted for Axis 1 variability, while coefficients of dispersion had 1.8 times less leverage in Axis 2.  With the incorporation into a spatial product and an associated database, this study provides a basis for defining statistically robust reference flow conditions for multiple flow metrics, against which current observed flows at specific sites may be compared.